Penelitian Evaluasi Di SMAN 1 Kota Probolinggo dalam Persiapan Turnamen Basket Walikota Cup - Roudhotul Janah; Agung Yudha Catur Rizal; Rosi Rosalina (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2023)
This study aimed to evaluate the preparations for the 2023 Mayor's Cup Invitation Basketball Championship. This study used a quantitative descriptive methodology. The subject of this study was the Principal of SMAN 1 Proboliggo City, which consisted of 1 person. Two extracurricular coaches, four people in charge of facilities and infrastructure, and 22 athletes. Information collection methods through questionnaires and written notes. The Pearson product-moment correlation test performed in SPSS at a significance level of 5% was used to verify the accuracy of the data. Data analysis involves using numerical descriptions with percentages to assess trend significance. Here are some ways to present the findings of the data analysis: 82% (18) of athletes rated "very good," 50% (1 person) of coaches ranked "very good," and 60% (3 people) of managers rated "good." Overall, 78% (2 people) rated the infrastructure condition as "very good," while 85% (2 people) rated the funding condition as "very good" (10 people). In conclusion, the condition of the city basketball team at SMAN 1 Probolinggo, both athletes, coaches, and administrators, has been optimal in preparing for the mayoral cup invitational basketball championship in 2023. Keywords: Basketball, Evaluation Research, Mayor's Cup